A study on HIV/AIDS infection and associated risks in young men who have sex with men - Vijaya Sorganvi; Rekha Udgiri (Al Ameen Medical College, 2017)
Background: In the global AIDS and HIV epidemic, prostitution has prevailing in discussions from many years. Sex workers generally have a high number of sexual partners. If they do become infected with HIV, they can likely pass it on to multiple customers. Globally it has been identified that the population of men who have sex with men had the high prevalence and incidence burden of HIV. Studies suggested the epidemic had peaked. Hence it is quite necessary to assess the magnitude of HIV infection and its related risk factors among sex workers. Aim and Objectives: To assess the Prevalence of HIV infection among STI patients and its associated risks in men who have sex with men. Methods: It was cross sectional study. 140 men who have sex with men registered with NGO in Vijayapura city were included. Results: The risk of HIV infection among those MSM who were unemployed, had their income less than Rs 5000 and those who had a past history of STD, Use of condoms and HIV prevalence were statistically associated. Conclusion: Requires more education about awareness about risk factors of disease of HIV/AIDS. Male sex workers are equally vulnerable to HIV/AIDS.